A Multiscale‐Model‐Based Near‐Term Prediction of Tropical Cyclone Genesis Frequency in the Northern Hemisphere. Issue 22 (15th November 2022) - Zhao, Jiuwei; Zhan, Ruifen; Wang, Yuqing; Jiang, Leishan; Huang, Xin
Abstract: Near‐term prediction of tropical cyclone (TC) activity is of great importance to formulate the long‐term plans for mitigating the potential TC‐induced damages. Here, we introduce a multi‐timescale regression model of TC genesis frequency (TCGF), which includes contributions by three interannual modes (El Niño‐Southern Oscillation, sea surface temperature anomalies over the eastern Indian Ocean and tropical North Atlantic), two interdecadal modes (the Atlantic Multidecadal Oscillation and the Interdecadal Pacific Oscillation), and a global warming mode. The model is shown to be able to capture well the present‐day multi‐timescale changes in TCGF in the major TC basins in the Northern Hemisphere. By combining the model and 100‐member simulations by the Max Planck Institute Earth System Model, we predict a robust increase in TCGF over the eastern North Pacific, an insignificant increase over the western North Pacific, and little change over the North Atlantic during 2020–2030 relative to 2009–2019. Plain Language Summary: How tropical cyclone (TC) activity will change in the next decade or so is especially important for government policymakers. However, the field on TC activity is very much in its infancy. Here we predict the near‐term changes in TC genesis frequency (TCGF) in the three main TC basins in the Northern Hemisphere, namely the western North Pacific, the eastern North Pacific, and the North Atlantic, by combining a new multi‐timescale regression model and the state‐of‐the‐art climate model projections. This regression model is constructed based on six key climate factors on different time scales, and can well reproduce the present‐day TCGF change during 1960–2019. The model predicts a significant increase in TCGF over the eastern North Pacific while insignificant change over the other two basins in the next 10 years. Key Points: We have developed a multi‐timescale regression model to represent changes in tropical cyclone (TC) genesis frequency (TCGF) The model can capture well the present‐day multi‐timescale changes in TCGF in the major TC basins in the Northern Hemisphere The model is used to conduct near‐term prediction of TCGF in the Northern Hemisphere by combining climate model projections